An AI-driven, de novo designed all-in-one nanoplatform for cold tumor therapy - Tian Lu; Ruining Jia; Yufei Wu; Yumeng Wang; Jiyi Zhang; Qiyu Chen; Ruonan Li; Yaonan Wang; Yuji Wang (Chemical Engineering Journal, 2026)

Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

Excavation-induced principal stress rotation and deformation responses in shallow-buried tunnels - Hongguang Jiang; Siwei Ruan; Ruining Liu; Xizhen Song; Yixin Li; Shun Liu; Xinyu Wang; Chenglu Gao; Zhanyong Yao; Chuanyi Ma (Transportation Geotechnics, 2026)

How did chlorine-resistant bacteria (CRB) grow on reverse osmosis membranes and cause fouling? - Yuan Bai; Yinhu Wu; Liwei Luo; Zhuowei Zhang; Ruining Wang; Haobin Wang; Zhuo Chen; Hongying Hu (Environmental Pollution, 2026)

An experimental and kinetic modeling study of the autoignition delay times of triethyl phosphite - Frederick Nii Ofei Bruce; Yuke Gao; Ruining He; Zhihan Zhu; Xin Wang; Yilin Zhao; Mengmeng Jia; Jiaxin Xie; Xin Bai; Yun Hin Taufiq-Yap; Chong-wen Zhou; Henry Curran; et al. (Fuel, 2026)

PccolyMOF dynamic fluorescent films with programmable photo-mechano responsiveness for visual stress mapping and multi-level information encryption - Jingzhi Wang; Youhao Wei; Menghan Mei; Yuanyuan Zi; Ruining Wang; Xiru Zhou; Yuhui Yang (Chemical Engineering Journal, 2026)

An exploration into the transplacental transfer of microplastics through placental transporters - Binbin Guo; Yawei Wang; Weilin Wang; Ruining Guan; Dongquan Li; Qiyue Wang; Chunyan Zhao (Journal of Environmental Sciences, 2026)

An experimental study on the ignition and combustion characteristics of ultrafine boron particles - Ruining He; Xin Bai; Xuan Ren; Yilin Zhao; Xin Wang; Jinhu Liang; Fei Qin; Ce Sun; Taufiq Yap Yun Hin; Chong-Wen Zhou; Henry J Curran; Yang Li (Fuel, 2026)

Corrigendum to “Flow backward alleviated the river algal blooms” [Volume 245, 15 October 2023, 120593] - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2026)

Heterogeneous diversification dynamics reshaped early Paleozoic marine evolutionary history - Minghao Du; Yong Wang; Jingqiang Tan; Wenhui Wang; Ruining Hu; Thomas J. Algeo; Richard A. Boyle; David A.T. Harper; Thomas Servais (Earth-Science Reviews, 2026)

Editor's note “Phosphorus – the main limiting factor in riverine ecosystems in China” [Sci. Total Environ. 870 (2023) 161613] - Yan Chen; Jie Chen; Rui Xia; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2026)

Liquid phase transformation mechanism of amphetamine initiated by •OH, HO2•, and 1O2 in advanced oxidation processes - Ruining Han; Peiwen Hu; Yan Wang; Chongwen Sun; Xuemin Zhao; Xiaomin Sun (Journal of Environmental Chemical Engineering, 2026)

Event-aware SWAT+ calibration for stormflows with monthly nutrient data in the Qingjiang River Basin - Ruining Wang; Xianqi Zhang; Hongyang Zhang; Yanbin Yang; Zelin Tao (Environmental Monitoring and Assessment, 2026)

An experimental and kinetic modeling study of the autoignition delay times of trimethyl phosphite - Frederick Nii Ofei Bruce; Zhihan Zhu; Ruining He; Xin Wang; Yuke Gao; Chong-Wen Zhou; Yun Hin Taufiq-Yap; Henry Curran; Yang Li (Fuel, 2026)

Advances in targeted nutrient delivery: materials design and mechanistic perspectives for precision nutrition - Yi Wang; Guannan Liu; Ruining Zhang; Yaqiong Wang; Pei Wang; Chong Xie; Hansong Yu; Runqiang Yang (Food Research International, 2026)

Integrated analysis of laboratory and field experiments to screen rice germplasm for submergence tolerance across various growth stages - Shengqin Liu; Hao Ai; Sumei Duan; Ruining Li; Edwin Afriyie Owusu; Liangliang Lv; Zhanglun Sun; Dachao Xu; Mengzhu Zhang; Aifeng Zhou; Wei Wang; Tingting Feng; et al. (Field Crops Research, 2026)

Ultraviolet-treated riboflavin induces ROS-mediated apoptosis via inhibiting mitochondrial complex I in acute myeloid leukemia - Ruining Liu; Shuang Ge; Jinyuan Sun; Yi Liu; Liping Sun; Yang Yu; Deqing Wang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Bifunctional modulation of MrBBX19 on repressor MrNAC47 and activator MrMYB12 for UV-B-mediated quercetin enhancement in Chinese bayberry (Morella rubra) - Ruining Zhang; Qianyu Wang; Jiajia Li; Jiafei Qian; Xiangrui Cui; Yunlin Cao; Yilong Liu; Xiaoyong Zhao; Di Wu; Changjie Xu; Kunsong Chen; Xian Li (Food Chemistry, 2026)

Citric acid modification of insoluble dietary fiber from soybean residue: Microstructural reconstruction, interfacial activity enhancement and stability by pickering emulsions - Ziyue Yu; Yuting Yang; Ying Zhang; Ruining Zhang; Bo Lyu; Sainan Wang; Wendan Jing; Hansong Yu (Food Research International, 2025)

Effects of high hydrostatic pressure on starch: multi-scale structures, interactions and applications - Yuqian Zheng; Xiaoyan Qin; Wenyan Wang; Zhilong Chen; Wenlong Xie; Jun Zhao; Ruining Zhang; Sheng Li (Food Chemistry, 2025)

The associations between landscape elements and soundscape perception: A meta-analysis - Ruining Zhang; Hui Ma; Chao Wang; Yuan Zhang; Jian Kang (Landscape and Urban Planning, 2025)

Pipe material significantly affected microbial regrowth and potential risks in reclaimed water distribution systems - Yuan Bai; Song Xue; Yinhu Wu; Haobin Wang; Ruining Wang; Lu Chang; Zhuo Chen; Hongying Hu (Journal of Hazardous Materials, 2025)

Soybean insoluble Fiber-EGCG binary compounds: Enhanced stability and synergistic antioxidant activity - Yi Wang; Ruining Zhang; Shidi Men; Mingzhe Li; Guannan Liu; Xiangbo Zeng; Bo Lyu; Sainan Wang; Hansong Yu (Food Chemistry, 2025)

Design and application of a reversible anti-biofouling coating: Toward sustainable and reusable medical devices - Hongxiao Shi; Ruining Zhang; Yuqian Gu; Yiguo He; Hongli Wang; Fuhao Shen; Haitao Deng; Jing Zhang; Dianyu Wang (Chemical Engineering Journal, 2025)

Nitrogen isotopic constraints on marine primary productivity across the Ordovician–Silurian transition - Jinqi Xu; Ruining Hu; Wenhui Wang; Xueqi Song; Haibo Xu; Jingqiang Tan (Chemical Geology, 2025)

Targeting thioredoxin reductase 1 by Andrographolide contributes to inducing ROS-mediated apoptosis in human NSCLC cells - Jiabing Wang; Kaiwen Jin; Nan Jin; Guran Lu; Ye Zhang; Yajie Wu; Zhiyi Zhou; Ruining Wang; Xueqiang Ma; Binhui Wang; Xi Chen (Chemico-Biological Interactions, 2025)

Dual-channel NIR self-illuminating nanoprobe for high-contrast imaging of reactive oxygen species in vivo - Hao Yuan; Hong Hu; Shengchun Sun; Jianxing Feng; Ning Shi; Yong Qiu; Ruining Yu; Yixian Wang (Chemical Engineering Journal, 2025)

MbWRKY50 confers cold and drought tolerance through upregulating antioxidant capacity associated with ROS scavenging - Xinhui Wang; Yingnan Li; Zhuo Chen; Longfeng Li; Qiqi Li; Zihan Geng; Wanda Liu; Ruining Hou; Lihua Zhang; Deguo Han (Journal of Plant Physiology, 2025)

Polystyrene and polyethylene perturb the structure of membrane: An experimental and computational study - Ruining Guan; Qiyue Wang; Dongquan Li; Binbin Guo; Weilin Wang; Ningqi Li; Jinlong Zhang; Ruitong Cai; Zeyang Cui; Haixia Zhang; Chunyan Zhao (Environmental Pollution, 2025)

Long-term soy dietary fiber diet modifies the intestinal internal environment: Focus on chronic ulcerative colitis - Yi Wang; Ruining Zhang; Mingzhe Li; Jiaxin Li; Guannan Liu; Sainan Wang; Bo Lyu; Hansong Yu (Food Research International, 2025)

Augmentation of antiviral immune response induced by perturbation of CD82 under microgravity condition - Yuzhi Zhang; Sijie Wang; Jiawei Chen; Yidan Zhou; Xiaoyu Yu; Ruining Peng; Longfeng Lu; Shun Li; Zhenhao Tian; Nu Zhang; Hui Yang (Fish & Shellfish Immunology, 2025)

D-Histidine modulated chiral metal-organic frameworks for discriminating 3,4-Dihydroxyphenylalanine enantiomers based on a chemiluminescence quenching mode - Xinyue Gao; Ruining Bai; Jin Yang; Shuai Luo; Hongwei Yuan; Lin Wang; Zhifeng Fu (Analytica Chimica Acta, 2025)

A Large-Scale Focused Fluid Flow Zone Between Atolls in the Xisha Islands (South China Sea): Types, Characteristics, and Evolution - Jixiang Zhao; Benjun Ma; Zhiliang Qin; Wenjian Lan; Benyu Zhu; Shuyi Pang; Mingzhe Li; Ruining Wang (Journal of Marine Science and Engineering, 2025)
A large number of seabed depressions, covering an area of 2500 km2 in the Xisha Massif of the South China Sea, are investigated using newly collected high-resolution acoustic data. By analyzing the morphological features and seismic attributes of the focused fluid flow system, five geological structures are recognized and described in detail, including pockmarks, volcanic mounds, pipes, faults, and forced folds. Pockmarks and volcanic mounds occur as clustered groups and their distributions are related to two large-scale volcanic zones with chaotic seismic reflections. Pipes, characterized by disordered seismic reflections, mainly occur within the focused fluid flow zone (FFFZ) and directly link with the large-scale deep volcano and its surrounding areas. Faults and fractures mainly occur along pipes and extend to the seafloor, commonly presenting lateral walls of mega-pockmarks. Forced folds are primarily clustered above volcanic zones and commonly restricted between faults or pipes, characterized by sediment deformations as indicated in seismic profiles. By comprehensive analysis of the above observations and a simplified simulation model, the volcanism-induced hydrothermal fluid activities are argued herein to contribute to these focused fluid flow structures. In addition, traces of suspected submarine instability disasters such as landslides have been found in this sea area, and more observational data will be needed to determine whether seafloor fluid flow zones can be used as a predictor of seafloor instability in the future.

Toxicity assessment and i-QSTTR analysis of ionic liquids on D. magna, D. rerio, and R. subcapitata - Ruining Guan; Ningqi Li; Ruitong Cai; Binbin Guo; Qiyue Wang; Dongquan Li; Chunyan Zhao (Science of The Total Environment, 2025)

A comprehensive experimental and theoretical study of thermal response mechanisms of TKX-50 and HMX - Xuan Ren; Ruining He; Xinhui Wang; Fang Wang; Xinpeng Zhang; Dingcheng Wang; Shuyuan Liu; Henry J. Curran; Jinhu Liang; Yang Li (Fuel, 2024)

Phage LysSA163-CBD mediated specific recognition coupled with ATP bioluminescence for the sensitive detection of viable Staphylococcus aureus in food matrices - Peng Guan; Ruining Li; Yifeng Ding; Chenxi Huang; Jia Wang; Hui Pan; Yanchun Shao; Xiaohong Wang (Analytica Chimica Acta, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

Targeting aberrant amino acid metabolism for pancreatic cancer therapy: Opportunities for nanoparticles - Xinlong Zang; Ke Lei; Jia Wang; Ruining Gong; Chao Gao; Zhenghui Jing; Jinxiao Song; He Ren (Chemical Engineering Journal, 2024)

Global assessment of radiative cooling and low-emissivity coatings for energy efficiency in buildings across all climate zones - Jiashuo Wang; Zekai Li; Tongyu Zhou; Wu Deng; Runqi Liang; Isaac Yu-Fat Lun; Yilin Li; Ruining Bao (Energy and Buildings, 2024)

Long-term global water pollution stress from crops production considering different driving forces - Chi Ma; Zhongwen Yang; Wenchao Sun; Rui Xia; Ruining Jia; Lu Wang; Yan Chen (Sustainable Production and Consumption, 2024)

Priority bacteria causing biofouling of reverse osmosis membranes: Potential disinfection-resistant bacteria and control strategies - Yujia Gao; Haobin Wang; Yuqing Xu; Ruining Wang; Han Liu; Yu Qiu; Yu Hong; Hongying Hu; Yinhu Wu (Desalination, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Coupling of nitrogen biogeochemical cycling and phytoplankton community structure before and after the Late Ordovician mass extinction in South China - Ruining Hu; Jingqiang Tan; Wenhui Wang; Xueqi Song; Philip A.E. Pogge von Strandmann; Jeffrey Dick; Chiyang Liu (Chemical Geology, 2024)

A critical review on the bioaccumulation, transportation, and elimination of per- and polyfluoroalkyl substances in human beings - Yao Lu; Ruining Guan; Nali Zhu; Jinghua Hao; Hanyong Peng; Anen He; Chunyan Zhao; Yawei Wang; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2024)

Probing the combustion kinetics of dimethylformamide: A theoretical study of H-atom abstraction reactions - Xin Bai; Yang Li; Shuyuan Liu; Ruining He; Jinhu Liang; Geyuan Yin; Shijie Zheng; Yan Qian; Xuebin Wang (Fuel, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

Flow backward alleviated the river algal blooms - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2023)

Depositional conditions of siliceous microfossil-rich shale during the Ordovician–Silurian transition of south China: Implication for organic matter enrichment - Ruining Hu; Jingqiang Tan; Jeffrey Dick; Yong Wang; Guolai Li; Chiyang Liu (Marine and Petroleum Geology, 2023)

Norfloxacin degradation in synthetic human urine using nickel converter slag-laterite heterogeneous Electro-Fenton process - Lingke Miao; Junfeng Li; Chengxiao Ma; Wenying Qu; Wenhuai Wang; Jiankang Wang; Ruining He (Journal of Water Process Engineering, 2023)

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Correction to: Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Infammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Inflammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Biological prevention and control of pitaya fruit canker disease using endophytic fungi isolated from papaya - Furun Wang; Ruining Zhang; Zhouyu Yuan; Ping Chen (Archives of Microbiology, 2021)

Magnetic biochar-based manganese oxide composite for enhanced fluoroquinolone antibiotic removal from water - Ruining Li; Zhaowei Wang; Xiating Zhao; Xi Li; Xiaoyun Xie (Environmental Science and Pollution Research, 2018)

Molecular Cloning and Identification of the 2′–5′ Oligoadenylate Synthetase 2 Gene in Chinese Domestic Pigs Through Bioinformatics Analysis, and Determination of Its Antiviral Activity Against Porcine Reproductive and Respiratory Syndrome Virus Infection - Ruining Wang; Hongfang Ma; Yinfeng Kang; Cunfa Li; Huawei Li; Erqin Zhang; Pengchao Ji; Jian He; Mengmeng Zhao (Indian Journal of Microbiology, 2018)